Studi Literatur Meningkatkan Hasil Belajar Matematika di Sekolah Dasar dengan Model Projects Based Learning (PJBL) - Kania, Anggun; Fadila, Rerey; Hasanah, Saidah; Alpian, Yayan (Peneliti.net, 2024)
The aim of this research is to re-analyze the use of project-based learning models to improve learning outcomes in mathematics subjects. The research method used is meta-analysis. Data collection was carried out by searching for articles, e-journals and papers using project based learning models, learning outcomes and mathematics research in basic education. The search results showed that there were 10 articles and e-journals and articles, but only 5 articles, e-journals and related articles analyzed the data using quantitative descriptive analysis. The analysis results show that the project -based learning model can improve student learning outcomes from a low of 11.30% to a high of 37.48% (average 24.72%).